An improved contrast source inversion approach for the reconstruction of single-pole Cole–Cole model parameters. Issue 15 (13th October 2022) - Liu, Guang-Dong; Hu, Yan-Ling; Yin, Jie
Abstract : Single-pole Cole–Cole empirical models are often used for the high-precision description of the dispersion characteristics of common media, such as biological tissues, and water. The existing contrast source inversion (CSI) methods are not appropriate to reconstruct their frequency-dependent electrical properties. Therefore, one of them, a multi-frequency (MF) CSI method with a multiplicative regularization (MR), is modified from the direct estimation of the contrast between dispersive scatterers and their background medium, into the alternative reconstruction of three kinds of one-pole Cole–Cole model parameters, namely, the optical relative permittivity, relative permittivity difference, and static conductivity. Through two two-dimensional (2D) numerical experiments, the modified CSI method has been applied to detect breast tumors. The reconstructed results demonstrate preliminarily that the improved approach is feasible for the quantitative inversion of the internal breast compositions, and thus promising for breast cancer screening.